Application of a stock control sheet in a food and nutrition unit - Franciane Pereira da Silva; Alyne Batista da Silva Galdino; Pryscila Araújo de Goes (Universidade do Estado do Rio de Janeiro, 2020)
Introduction: the professional nutritionist has the tasks of planning menus and, consequently, stock control. Among countless activities inherent to the collective food sector, the importance of supply management can go unnoticed and cause problems in the execution of the menus, generating monotony in them. So, control tools are needed, since food monotony can cause health problems for users. Objective: this study aimed to present the preparation and implementation of a stock control spreadsheet in a food and nutrition unit (FNU) of a public higher education institution. Methods: the study was developed and carried out at the Restaurante Universitário da Escola Agrícola de Jundiaí (University Restaurant of the Agricultural School of Jundiaí), of the Universidade Federal do Rio Grande do Norte (Federal University of Rio Grande do Norte), located in the District of Jundiaí, Macaíba, Rio Grande do Norte, Brazil, with a survey of control cards. Results: the product of this study was a spreadsheet in Excel® format to control dry foodstuffs from the stock. It was observed that in addition to controlling the entry and exit of the genders, the spreadsheet also helped in the decision to purchase and replenish supplies. Conclusion: in view of the desired objectives, the spreadsheet was developed and applied successfully, reaching the purpose expected by the service.